CRITERIA FOR TYPOLOGY OF CONCEPTS IN THE LEGAL DISCOURSE - Fedulova, M.N. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The public relations are based on a particular system of values which is brought to the society through different conceptual spheres articulated by its own specific semantic area of language. The author says that the semantic area of language and the semantic structure of legal discourse are the reflection of the conceptual sphere of law and can be considered as a criteria in the conceptual analyze of legal language. The problem is to choose a correct criteria for typology of concepts in the legal discourse as a special discourse. Taking into consideration that the legal discourse is a social regulator the cumulative component that depends on a correct lexical unit is very important. The cumulative component is an in-formative intensity of the word semantics that is very important for regulation of public relations. The con-ceptual sphere of the legal discourse is characterized by some specific features. The article says that in addi-tion to the common ontological criteria characterizing any discourse the criteria of semantic intensity can be a base of typology of concepts in the legal discourse. The criteria of semantic intensity, concept volume can be seen in direct (terminological) and in indirect (narrative) forms of expressive repre-sentation in any text.